Study on the Effects of Powder-Liquid Ratio and Cement Ratio on Mechanical Properties and Microscopic Characteristics of Polymer-Cement Composite. (24th December 2021) - Huang, Zhe; Xu, Jinyu; Leng, Binglin; Ren, Weibo; Chang, Sen; Wang, Zhihang; Xia, Wei
Abstract : This paper is about a study on the mechanical properties of a new polymer-cement composite (PCC) in constant elongation, tension, and shear. The study explored the effects of powder-liquid ratio and cement ratio on the mechanical properties of PCC through detecting the strength, deformation, and energy consumption of specimens under different powder-liquid ratios and cement ratios. In addition, scanning electron microscope and mercury injection apparatus were used for an in-depth analysis on the micromorphology and pore structure features of PCC under different powder-liquid ratios and cement ratios to explore the influence of powder-liquid ratio and cement ratio of the micromechanical properties of PCC. The results showed that, with the increase of powder-liquid ratio and cement ratio, the constant elongation adhesion strength of PCC decreased, and, at a high powder-liquid ratio (0.55) or a high cement ratio (0.5), the constant elongation adhesion strength of PCC completely disappeared. Meanwhile, with the increase of powder-liquid ratio and cement ratio, the tensile shear strength of PCC increased, while the deformation capacity of PCC decreased. The optimal ranges of powder-liquid ratio and cement ratio for PCC were 0.35–0.4 and 0.3-0.4, respectively. Furthermore, the increased powder-liquid ratio and cement ratio made the total pore volume decreased and pore structure refined, which improved the compactness of PCC, thus influencing the performance of PCC macroscopically. An achievement for the study is a flexible composite material, which was formulated with the polymer film as continuous base phase, as well as the inorganic composition and cement hydrates as dispersion phase. The material can effectively improve the economy and practicability of cementation of fissures for airfield pavement.